2003
DOI: 10.1614/0043-1745(2003)051[0557:eopcra]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of purple (Cyperus rotundus) and yellow nutsedge (C. esculentus) on growth and reflectance characteristics of cotton and soybean

Abstract: Because of interest in monitoring crop response to weed interference, greenhouse experiments were conducted to evaluate interference of purple and yellow nutsedge on the growth, development, and spectral response of cotton and soybean. Cotton fresh weight was reduced 9 to 42% compared with the control when grown with yellow and purple nutsedge. Fresh weight of soybean was reduced 27 to 60% when it emerged simultaneously with yellow nutsedge and 45 to 63% when it emerged 7 d after yellow nutsedge. Soybean fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It may be possible to find reflectance response patterns of individual weed species that would create new possibilities in site-specific weed management. Classification of weeds in crop and rangeland areas by remote sensing techniques has been accomplished (Chang et al 2004;Everitt et al 1995;Gibson et al 2004;Henry et al 2004b;Lass et al 1996;Lass and Callihan 1997;Leon et al 2003;Menges et al 1985;Smith and Blackshaw 2003;Vrindts et al 2002;Williams and Hunt 2002). found that simulated sitespecific herbicide management in nontransgenic and transgenic soybean production systems resulted in higher estimated net gains than broadcast herbicide management.…”
mentioning
confidence: 99%
“…It may be possible to find reflectance response patterns of individual weed species that would create new possibilities in site-specific weed management. Classification of weeds in crop and rangeland areas by remote sensing techniques has been accomplished (Chang et al 2004;Everitt et al 1995;Gibson et al 2004;Henry et al 2004b;Lass et al 1996;Lass and Callihan 1997;Leon et al 2003;Menges et al 1985;Smith and Blackshaw 2003;Vrindts et al 2002;Williams and Hunt 2002). found that simulated sitespecific herbicide management in nontransgenic and transgenic soybean production systems resulted in higher estimated net gains than broadcast herbicide management.…”
mentioning
confidence: 99%